DETEKSI KRISIS KEUANGAN PERUSAHAAN SEKTOR PERBANKAN DI INDONESIA - Dati, Qidida Sela; Mirzayatiq, Kholisa; Fitriana, Citra Agis; Raharja, Bayu Sindhu (Jurnal Analisis Bisnis Ekonomi, 2018)
Altman Z-Score is a method of scoring bankruptcy. The bankruptcy prediction method that will be used in this study is the Altman Z-Score method that is in accordance with the financial ratios which also have a cut-off point to determine the value of bankruptcy. This study uses five ratios, that is Capital Adequacy Ratio (CAR) to the Asset Sector (X1), Earnings Balance on Total Assets (X2), EBIT to Total Assets (X3), Market Value of Debt Book Value (X4), and Interest Income on Total Assets (X5). This research is a descriptive study conducted on 32 banks listed on the Indonesia Stock Exchange. Financial reports for 2013-2016 Taken from the official website of the Indonesia Stock Exchange (IDX) and the Indonesian Capital Market Directory (ICMD) then bankruptcy analysis is used the Altman Z-Score modification model. Based on the results of research and discussion that has been carried out, it can be concluded from 2013-2016 that banks in a healthy condition is 22.66%, banking in gray areas or gray is 34.38%, and bankrupt is 42.97 %.